Faculty and student perceptions of the use of web 2.0 tools to develop communication skills in English - Laura Chagas (Universitat Politècnica de València, 2021)
As the use of Web 2.0 proves to be beneficial in foreign language learning contexts, this quantitative study focuses on the use of Web 2.0 tools for the development of communication skills in English, specifically in higher education. In order to investigate the participants’ perceptions, 341 undergraduate students and 70 faculty members from Portuguese higher education institutions responded to an online survey. They were asked to associate a list of Web 2.0 tool types to the communication skills they believed that could be developed in English language learning.